PENGARUH PENINGKATAN DOSIS PUPUK TRICHOKOMPOS JERAMI PADI TERHADAP PERTUMBUHAN TANAMAN KANGKUNG DARAT (Ipomea reptans Poir) - Muhammad Zikri; Adiwirman Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aimed to determine the best dose of trichocompost rice straw for the growth and production of water spinach. The research was conducted at the Faculty of Agriculture University of Riau's experimental station, from 1 to 31 August. This study used a one-factor randomized block design (RBD) with 5 treatments and 4 replications so that it consisted of 20 experimental units. The parameters observed were plant height, leaf number, fresh weight, root volume, leaf area and root canopy ratio of the plant. Data were analyzed using variance and continued with HSD test at the 5 % level. The doses of trichocompost rice straw alteration significantly increased plant height, leaf number, fresh weight, root volume, leaf area and the root canopy ratio of land water spinach. The doses of trichocompost rice straw 12 tons. Ha-1 was the best dose to those increased plant height, leaf number, fresh weight, root volume, leaf area and the root canopy ratio of water spinach. Keywords: Ipomea reptans Poir, trichocompost of rice straw